Agricultural co-operatives: perspectives for the 21st Century - B. Boučková (Agricultural Economics (AGRICECON), 2002)
Agricultural co-operatives play an important role in the European Union, as can be proved by their numbers in the individual EU countries. However, they have diversified during the last decades and developed from the "classical" co-operative of the Rochdale type into several forms, which do not always fully observe all the recognised co-operative principles. These are namely the share co-operatives, daughter co-operatives, "New Generation Co-operatives" and limited liability co-operatives. Among the individual EU countries, there are also considerable differences with regard to the co-operative legal frame. For the future, co-operatives can play important role both in the economic field and in the social field.